(3QSGdI GdCOH eY GddWGaI aj UMI GdLeYI HeSGLO GdbQGaIs - (3YHO Gddg Hf MSjf NGWQ GdYOhjs ((3eMehO Hf YHOGdQMef GdTQja GdYOhj Hdg GdeGdcj s)
(3ChdgG (B:s
(3CeG HYO agP cdeGJ jSjQI LeYgG cGJHgG GdabjQ YHOGdbGVj GdeGdcj GdYOhj Ydi MSH ageg hbUhQg hSeGgG QSGdI GdCOH eY GddWGaI aj UMI GdLeYg HeSGLO GdbQGaI s
(3BNQgG (B:s
(3JLH Ydjge aj ecGfge hdGJUM efgehGddg CYde HGdUhGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg eGdc (B241) s
Keywords: (3Gdabg GdeGdcjs